2019
DOI: 10.9734/ajrcos/2018/v2i430078
|View full text |Cite
|
Sign up to set email alerts
|

The Architectural Dynamics of Encapsulated Botnet Detection (EDM)

Abstract: Botnet is one of the numerous attacks ravaging the networking environment. Its approach is said to be brutal and dangerous to network infrastructures as well as client systems. Since the introduction of botnet, different design methods have been employed to solve the divergent approach but the method of taking over servers and client systems is unabated. To solve this, we first identify Mpack, ICEpack and Fiesta as enhanced IRC tool. The analysis of its role in data exchange using OSI model was carried out. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…However, the era also saw the introduction of Open System Interconnection (OSI) model to which has become the adherence model by all computing gadgets manufacturers and this model over the years has bridged the gap. OSI is a seven layer model which demonstrates how information is to be transmitted between two or more connected devices [4,5]. The OSI model has largely revolutionized data communication thereby giving room for communication exploration in an out of remote area.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the era also saw the introduction of Open System Interconnection (OSI) model to which has become the adherence model by all computing gadgets manufacturers and this model over the years has bridged the gap. OSI is a seven layer model which demonstrates how information is to be transmitted between two or more connected devices [4,5]. The OSI model has largely revolutionized data communication thereby giving room for communication exploration in an out of remote area.…”
Section: Related Workmentioning
confidence: 99%
“…The cry for the integration of Information and Communication Technology into school learning curriculum has further raised the hope of people on maximum productivity of teaching staff in tertiary institution. However, this Osagie et al; AJESS, 5(3): 1-10, 2019; Article no.AJESS.51942 2 seems to be eluding because, institutions on yearly basis produced students who are not ICT oriented, thereby, leaving the general public with question of teacher's productivity. In this paper, a survey was conducted to ascertain the level of ICT compliance on teaching staff productivity and in addition, review was carried out to know if ICT has direct impact on teaching quality as well as proffer possible solutions that could aid smooth delivering of teaching methodology (that is ICT compliance).…”
mentioning
confidence: 99%
“…Many reasons abound for students' quest on computer education. Though, series of drawbacks (insecurity issues) are some of the reasons [27,28] Modernizing Education: There is no comparative disadvantage on the old method of teaching over the modernize approach to teaching in the 21 st century; rather, the modernized approach has superior advantage over the ancient method. Prior to the discovering of classroom technologies, many classrooms' teaching in the developing countries where awkward and disgusting and this was because it failed to produced competitive children with the developed countries.…”
Section: (B) the Need For School Children Computer Educationmentioning
confidence: 99%
“…Networks of different kinds have different configurations with its operational scope based on the fundamental principle of the intended user [7]. The internal mechanism of the design structure of a network is usually not for public consumption and this is because there are inherent attributes of the security apparatus that prevent it from been hacked or accessed by unauthorised user [8]. Notwithstanding, as internet provides access to network of different kinds through authentication it also provides several opportunities to accessing network without following the structural rules of the security architecture [8].…”
Section: Introductionmentioning
confidence: 99%
“…The internal mechanism of the design structure of a network is usually not for public consumption and this is because there are inherent attributes of the security apparatus that prevent it from been hacked or accessed by unauthorised user [8]. Notwithstanding, as internet provides access to network of different kinds through authentication it also provides several opportunities to accessing network without following the structural rules of the security architecture [8]. Practical studies have shown serious vulnerability of some network infrastructures and the unwillingness on the part of the affected ---networks to disclose these information(s) gave rise to thousands of illicit acts within and outside the cyberspace (network).…”
Section: Introductionmentioning
confidence: 99%